2021
DOI: 10.5530/pj.2021.13.83
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Phytochemical Studies, GC-MS Analysis and In vitro Antioxidant Activity of Selected Medicinal Plants and its Polyherbal Formulation

Abstract: Background: Novel polyherbal formulation (PHF) is the utilization of more than one herb in the preparation of herbal medication. The thought is found in the conventional system of medicine where the variety of herbs in a specific proportion of illness. Because of synergism, polyherbalism presents a few advantages which aren't accessible in single herbal medication. It is utilized in these medications for the treatment of numerous sicknesses including antioxidants. Objective: To develop a phytochemical screenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…For example, the TPC of a polyherbal formulation prepared from various proportions of Centella asiatica (L.) Urb., Piper sarmentosum Roxb., and Morinda citrifolia L. ranged from 107.15-167.15 g GAE/ml, with individual TPC of 134.33, 125.7, and 209.12 g GAE/ml, respectively (16). Our result is also similar to the study reported that the TPC of a polyherbal formulation was within the range of those of its components (17).…”
Section: Discussionsupporting
confidence: 90%
“…For example, the TPC of a polyherbal formulation prepared from various proportions of Centella asiatica (L.) Urb., Piper sarmentosum Roxb., and Morinda citrifolia L. ranged from 107.15-167.15 g GAE/ml, with individual TPC of 134.33, 125.7, and 209.12 g GAE/ml, respectively (16). Our result is also similar to the study reported that the TPC of a polyherbal formulation was within the range of those of its components (17).…”
Section: Discussionsupporting
confidence: 90%
“…Phytochemical characterization is an immensely valuable step in detecting and quantifying novel bioactive compounds from in vitro-derived tissues (callus, somatic embryo and other plant parts). The application of GC–MS-based chemical profiling for the recognition and documentation of a diverse array of phytochemicals has been exemplified in many scientific reports [ 32 , 33 , 34 ]. In the present study, the GC–MS-based comparative analysis of the metabolites of tissue culture and field-grown (mother) plants was conducted in order to obtain the phytochemical profiles of two alternative sources of T. indica plants.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-oxidant assay was done by using the methods explained in previous studies. DPPH ● scavenging activity [ 30 ], Hydrogen peroxide scavenging activity [ 31 ], Hydroxyl radical scavenging activity [ 32 ], Metal chelating activity [ 33 ], Nitric oxide scavenging activity [ 34 ], Ferric reducing power [ 34 ], and Total antioxidant activity [ 26 ].…”
Section: Methodsmentioning
confidence: 99%